(untitled) (DINAMIS, 2025)
A substantial amount of coffee plantation waste is generated in Aceh highland, yet its utilization remains limited. Most of the wastes are dumped on the ground, while coffee parchment is often burned without further application. This study explores the conversion of coffee parchment into briquettes, focusing on their combustion characteristics. The parchment were subjected to torrefaction process at temperatures ranging from 240°C to 270°C and then ground to particle sizes of 40, 60, and 80 mesh. Briquettes were formed using 10% tapioca flour as a binder and compressed simultaneously for 20 pieces of briquettes at pressures of 300, 400, and 500 kg/cm². The resulting briquettes, with dimensions of 37×28×28 mm, exhibited a density of 0.63 g/cm³ and a combustion rate of 0.37 g/min, enabling a burn duration of up to 105 minutes and a peak temperature of 435°C. The best performance was achieved using a particle size of 60 mesh and a compaction pressure of 400 kg/cm². These findings demonstrate the potential of coffee parchment as a viable source of solid fuel for heating applications.